Evaluation of the Spectrum of Proteolytic Activity of Micromycetes of the Genus Aspergillus in Relation to Proteins of the Hemostasis System - Osmolovskiy, A.A.; ŞAŞ, B.; Aleksandrova, A.V.; Baranova, N.A.; Kreyer V.G. (Pleiades Publishing, 2022)
Abstract: The activity of extracellular proteinases in seven strains of different species of micromycetes of the genus Aspergillus in relation to proteins of the hemostasis system was studied. Comparison of the values of enzymatic indices during the growth of strains on agar media with casein and fibrin, followed by their submerged fermentation fermentation and analysis of amidolytic activity with chromogenic peptide substrates of proteinases of the hemostasis system, made it possible to select the A. candidus A4 and A. crustosus A29 strains as promising producers of fibrinolytic proteinases. The proteinases formed by both strains were able to cleave the chromogenic peptide substrates of thrombin, plasmin, factor X, protein C, and urokinase, exhibiting high plasmin-like and thrombin-like activity and not having an activating effect on the proenzymes of the hemostasis system. © 2022, Allerton Press, Inc.
Keywords: Chromogenic Peptide Substrates; Fibrinolytic Enzymes; Hemostasis Protein Activators; Micromycete Proteinases; Plasmin-like Activity; Thrombolytic Agents